G. P. FEDOTOV ON THE TRANSFORMATION OF THE RUSSIAN GOVERNING ELITE - E. M. Amelina (Вестник университета)
The article analyses the transformation of the Russian management elite from the point of view of the famous Russian historian, sociologist and philosopher G. P. Fedotov (1886–1951). The paper discloses the civilizational features and stages of the evolution of the elite. The author reveals social, psychological, mental and other characteristics given by the thinker to the main domestic types of managers such as: a Russian European, a “Moscow man” and a Soviet manager. The study shows his positive assessment of the management culture of the nineteenth century. The article considers the thinker’s views on the processes of transformation and primitiveness  of management personnel of the early 20th century. The paper analyses the portrait of the Soviet manager given by G.P. Fedotov. The author shows the utilitarianism and Americanism of his social aspirations, which give rise to  socialist bourgeoisness. The study reveals the significance of the analysis conducted by the thinker.